A hybrid online signature verification system supporting multi-confidential levels defined by data mining techniques. (8th November 2010) - Moon, Ji Hwan; Lee, Sung Gyu; Cho, Sung Young; Kim, Yoo-Sung
Online signature verification is used widely for user authentication in many applications. In existing systems, one confidential level is usually used as the threshold for signature verifications. This causes high false rejection ratio (FRR) to systems in which signature verification is less important, and on the other hand, high false acceptance ratio (FAR) to systems in which signature verification is more critical. Thus, applying multi-confidential levels to the signature verification is crucial to solve this problem. Also, data mining techniques can be used to appropriately define multi-confidential levels. This paper proposes a hybrid online signature verification system supporting multi-confidential levels defined by data mining techniques.